Muhammadiyah Education Update Integration Of Islamic Values And Global Challenges In The Digital Era - Atabik Luthfi; Hardjadinata; Deden Edi; Fajar Harguna Endra Putra; Siti Uswatun Hasanah; Murodi; Ilham Sentosa (Institut Agama Islam An-Nawawi Purworejo, 2025)
Muhammadiyah's educational renewal movement is a dynamic response to the development of the times and the needs of the community, especially in facing global challenges in the digital era. In an effort to integrate Islamic values with advances in technology and information, Muhammadiyah continues to innovate in systems, curriculum, and learning methods. However, the reality in the field shows that this renewal process still faces various obstacles. One of them is the low achievement of learning outcomes, where around 50% of Muhammadiyah high school students have not achieved the Minimum Completion Criteria (KKM) set. This phenomenon reflects the gap between the vision of progressive education and actual implementation in schools. The study used a qualitative method with a Research & Development (R&D) approach. This study aims to analyze Muhammadiyah's educational renewal strategy in integrating Islamic values and responding to global challenges, as well as evaluating the factors that cause low student academic achievement. These findings are expected to contribute to strengthening the Muhammadiyah education model that is holistic, adaptive to the digital era, and oriented towards the character and achievements of students.